Preference for HIV testing among community residents in Yunnan Province, China: results from a discrete choice experiment - Jingwen Yang; Chenquan Qiu; Renhai Tang; Wenbin Dong; Enlong Yao; Huyunzhao Wang; Shuwen Lin; Minyang Xiao; Zuyang Zhang; Jin Niu; Liru Fu; Lijun Song; et al. (BMC Health Services Research)
Abstract Background The detection and early identification of people living with HIV/AIDS (PLWH) and their rapid engagement in antiretroviral treatment are indispensable for fighting HIV transmission. This study aimed to elicit preferences regarding HIV testing among community residents to identify a model of community-based HIV testing services that would appeal to this population. Methods A discrete-choice experiment (DCE) was conducted in the communities of Yunnan Province, China. The participants were asked to make nine choices between two unlabelled alternatives that differed in seven attributes: distance to the testing venue, confidentiality, institution, administrator, support services, testing days, and testing cost. The data were analysed using a random parameter logit model. The preference regression coefficient (β) was used to compare the importance of attribute levels. Relative importance (RI) was used to indicate the degree of importance of each attribute to the participants. Results The results indicate confidentiality was the most important attribute (RI = 39.21%), followed by testing cost (RI = 25.15%), administrator (RI = 11.91%), institution (RI = 11.29%), support services (RI = 8.02%), distance (RI = 4.25%), and testing day (RI = 0.16%). The participants in our study showed a preference for confidentiality regarding the testing status (β = 1.82, p < 0.001), for the test being available at hospitals (β = 0.72, p < 0.001), and for the test being administered by physicians (β = 0.74, p < 0.001). We also observed that having support services was preferable (β = 0.50, p < 0.01) to support services not being available. Free HIV testing was the most preferred cost attribute (β = 1.61, p < 0.001). The distance and testing days were not significantly different (p > 0.05). Conclusions Community residents preferred an HIV testing service run by physicians in high-level health care institutions with excellent confidentiality, low cost, and available support services. Confidentiality remained the most important attribute of the HIV testing service. Worrying that others know the test results is a significant factor influencing testing decision-making and the uptake of testing services. Adjusting the model of community-based HIV testing services according to the preferences of the target population could make it more efficient and effective for the general public, allowing for early detection of HIV infection.